2008
DOI: 10.2135/cropsci2007.08.0476
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Selection for Vegetative Phase Change in Maize and Indirect Effects on Response to Puccinia sorghi

Abstract: In maize (Zea mays L.), some experiments have indicated that early vegetative phase transition is associated with increased resistance to disease, insects, and stalk lodging. The sweet corn population Minn11 was selected over three cycles of divergent recurrent selection for early‐phase transition and late‐phase transition. Objectives were to determine the effectiveness of divergent recurrent selection and if the divergent selection program was associated with resistance to common rust (Puccinia sorghi). Selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…The lack of a correlation between LLJW and rust damage agrees with the fi ndings of Abedon and Tracy (1998) and Chandler and Tracy (2007), but it is in contrast to the fi ndings of , Basso et al (2008), and Riedeman et al (2008), who found a signifi cant correlation. Overall, none of the phase change measurements were correlated with any of the non-phase change traits.…”
Section: Early Maturity Trialssupporting
confidence: 78%
“…The lack of a correlation between LLJW and rust damage agrees with the fi ndings of Abedon and Tracy (1998) and Chandler and Tracy (2007), but it is in contrast to the fi ndings of , Basso et al (2008), and Riedeman et al (2008), who found a signifi cant correlation. Overall, none of the phase change measurements were correlated with any of the non-phase change traits.…”
Section: Early Maturity Trialssupporting
confidence: 78%
“…and European corn borer ( Ostrinia nubilalis Hubner) are common yield‐reducing factors in maize (Dicke and Guthrie, 1992; Smith and White, 1992). The relationship between adult vegetative tissue and common rust resistance was demonstrated by Abedon and Tracy (1996) and Basso et al (2008) Resistance to insects such as European corn borer, fall armyworm ( Spodoptera frugiperda J.E. Smith), and southwestern corn borer ( Diatrea graniosella ) has also been linked to vegetative phase change (Lawson and Poethig, 1995; Abedon and Tracy, 1996; Williams et al, 1998, 2000).…”
mentioning
confidence: 99%
“…Mutant genes such as glossy and corngrass delay the transformation to cuticular wax and appeared to delay expression of resistance to common rust (Abedon and Tracy, 1996). Basso et al (2008) inoculated common rust at different stages of leaf development in populations selected for early vs. late change to the cuticular wax and also suggested their association with timing and severity of rust infection. We could not confirm this type of behavior for southern rust in Hawaii, including mutants for glossy and corngrass .…”
Section: Southern Rust In Hawaiimentioning
confidence: 94%
“…Urediospore infection by rusts requires extended dew periods and is evidently affected by the manner in which water films occur on grass leaves. Tracy and colleagues (Abedon and Tracy, 1996; Basso et al, 2008) have researched leaf waxes and suggested their relationship to rust tolerance. Young corn leaves (first 5 to 8) have an epicuticular wax that causes water to bead up in tiny droplets while mature leaves have a star‐shaped cuticular wax that causes water to spread in a thin, rapidly drying film that ostensibly might inhibit rust infections.…”
Section: Southern Rust In Hawaiimentioning
confidence: 99%